2016
DOI: 10.1039/c6ra00454g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the water extract of waste papaya bark ash and its implications as an in situ base in the ligand-free recyclable Suzuki–Miyaura coupling reaction

Abstract: The conversion of waste papaya-bark to ash–water extract via low-temperature combustion, and its utilization as an efficient and eco-friendly in situ basic medium for Suzuki–Miyaura cross-coupling reaction at room temperature are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…[36] It was reported that roots, bulbs, and leaves contain a large distribution of K, Na, Mg, Ca, and P. [36] However, a detailed characterization of the water extract reveals a comparatively higher weight percent of alkali metals than that of various reported waste biomass like banana peels, decayed papaya bark, rice straw etc. [38][39][40] The exceptional property of this AWEH (Ash Water Extract of Water Hyacinth) may likely be due to the formation of metal oxides Figure 1.Preparation of water extract and their activity in Suzuki-Coupling or hydroxides in their ash water extract that imparts outstanding basicity which directs the coupling reaction to an external base free condition. As such the water extract (AWEH) contributes a dual role in the synthesis of biaryl derivative, i.e via in situ base cum reaction media (solvent system).…”
mentioning
confidence: 99%
“…[36] It was reported that roots, bulbs, and leaves contain a large distribution of K, Na, Mg, Ca, and P. [36] However, a detailed characterization of the water extract reveals a comparatively higher weight percent of alkali metals than that of various reported waste biomass like banana peels, decayed papaya bark, rice straw etc. [38][39][40] The exceptional property of this AWEH (Ash Water Extract of Water Hyacinth) may likely be due to the formation of metal oxides Figure 1.Preparation of water extract and their activity in Suzuki-Coupling or hydroxides in their ash water extract that imparts outstanding basicity which directs the coupling reaction to an external base free condition. As such the water extract (AWEH) contributes a dual role in the synthesis of biaryl derivative, i.e via in situ base cum reaction media (solvent system).…”
mentioning
confidence: 99%
“…Although recently some efficient methodologies have been developed for SMC by avoiding external base and ligands, there is still a demand to develop new synthetic protocols since unexpected results can be seen in SMC by a small change of reaction conditions like temperature, ligand, base, nature of substrates, solvent, etc . Typical trends in substrate selectivity and reactivity may be broken .…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Nevertheless, most of these are operated in harsh conditions [41] or require organic solvents [42,43] and additives such as surfactants [44,45] and polymers. [46] Although recently some efficient methodologies have been developed for SMC by avoiding external base and ligands, [47][48][49][50][51][52][53][54] there is still a demand to develop new synthetic protocols since unexpected results can be seen in SMC by a small change of reaction conditions like temperature, ligand, base, nature of substrates, solvent, etc. [55] Typical trends in substrate selectivity and reactivity may be broken.…”
Section: Introductionmentioning
confidence: 99%
“…Green chemistry in the past two decades playing important environmental impact, and continuous effort to come up with an alternative methodology that minimizes use of the hazardous solvents during chemical synthesis and reduction of reaction time [1]. Therefore in the recent year's use of agro-waste stuff ash extract as a chemical surrogates becomes one of the most exciting discoveries of organic chemists [2]. Many authors reported a novel route for the Suzuki-Miyaura cross-coupling reactions using water extract of banana peel ash (WEB) as solvent system as well as in situ base for the reaction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%